2000
DOI: 10.1203/00006450-200012000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Long-Time Persistence of Superantigen-Producing Staphylococcus aureus Strains in the Intestinal Microflora of Healthy Infants

Abstract: Staphylococcus aureus has been isolated at an increasing rate from infants' stools during the last decades, but it is not known whether this species can colonize and persist in the intestinal microflora. To investigate this, 49 Swedish infants were followed prospectively from birth until 12 months of age. S. aureus was identified in a rectal swab obtained 3 d after delivery and in quantitative cultures of fecal samples collected at 1, 2, 4, and 8 weeks and at 6 and 12 months of age. A random amplified polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
101
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 47 publications
(40 reference statements)
8
101
1
Order By: Relevance
“…Of S. aureus strains colonising the neonatal gut, approximately 45% have the capacity to produce a toxin with superantigenic function [16,17]. We have not noted any untoward effect of such colonisation, as parents report no increased prevalence of gastro-intestinal or other symptoms [17]. Quite unexpectedly, we instead found that infants colonised in the first week(s) of life with S. aureus had significantly decreased risk of developing food allergy [20].…”
Section: Introductionmentioning
confidence: 51%
See 3 more Smart Citations
“…Of S. aureus strains colonising the neonatal gut, approximately 45% have the capacity to produce a toxin with superantigenic function [16,17]. We have not noted any untoward effect of such colonisation, as parents report no increased prevalence of gastro-intestinal or other symptoms [17]. Quite unexpectedly, we instead found that infants colonised in the first week(s) of life with S. aureus had significantly decreased risk of developing food allergy [20].…”
Section: Introductionmentioning
confidence: 51%
“…Statistics from SEA pretreated OVA-fed mice as compared with sham-treated OVA-fed mice are shown as à po0.05. SEA is the most potent superantigen [32] and because SEAproducing strains are more common than SEB-producing strains in the gut flora of Swedish children [17], SEA was used in this study. However, we also investigated the effect of SEB pretreatment in our model of oral tolerance and airway allergy and found that SEB was less effective and less reliable in improving oral tolerance compared with SEA (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Superantigenic-producing S. aureus incorporated into the digestive tracts might cause enterocolitis (Watanabe et al, 2001) and persist for a long time in the intestinal microbiota of infants (Lindberg et al, 2000). Enteric TSST-1 activates systemic T cells and leads to a dysregulated, but exuberant immunological activity causing the remission and flare-up cycle of mucosal inflammation in patients with ulcerative colitis (Shiobara et al, 2007).…”
Section: Introductionmentioning
confidence: 99%